Implementasi Nilai Nilai Kebangsaan Bersumber UUD 1945, NKRI, dan Bhinneka Tunggal Ika Guna Menerapkan Kebijakan Kesehatan, Keselamatan, Keamanan & Lingkungan (HSSE) di PT. Pertamina (Persero) - Dian Putri Wulandari; Edy Soesanto; Jihan Nur Afiyah (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2024)
PT. Pertamina (Persero) isl a lState-Owned lEnterprise (BUMN) thatl produces raw materials such as fuel, kerosene, LPG (liquefied fuel gas), LNG (liquefied natural gas), and petrochemical products. Articlel 33 paragraphl (3) ofl the 1945l Constitution confirms thatl the learth, lwater, and naturall resourcesl containedl therein arel controlledl byl the statel andl usedl for thel greatest lprosperity of thel people. This lawl gives the state thel authority to manage natural resources in the public interest and the welfarel of alll people in relation tol the context ofl social justice. However, the implementation of this law requires strict and transparent supervision to ensure that natural resources are actually used appropriately and fairly for all stakeholders and that uncontrolled environmental damage does not occur. This studyl aims tol find outl how human lvalues, which are reflected inl the 1945l Constitution, Unitaryl State olf the Republicl of Indonesial (NKRI), and Bhinneka Tunggal Ika are implemented in the Health, lSafety, Security, andl Environment (lHSSE) program at PT. lPertamina. Focus is also given to efforts to ensure the effectiveness and smooth implementation of the policy. Law Numberl 13 ofl 2003 concerningl Manpower and Lawl Number 1l of 1970l concerning lOccupational Safety andl Health (K3) are described in the State Gazette. PT. Pertamina is committed to carrying out refinery, petrochemical and infrastructure project operations planned safely and environmentally by applying high standards to aspects of Health, Safety, Security & Environment (HSSE) in accordance with moral values, market demands, needsl and expectationsl of customersl and stakeholdersl to supportl thel achievementl of thel company's goals, visionl and mission. The methodl used inl this studyl is thel Literature Studyl approach. In the literature study, the datal used is secondary data in the form of article data from PT. Pertamina (Persero) and various other existing sources. Thel results ofl the study, thel HSSE functionl at PT Pertaminal (X1), and effective management of Natural Resources for prosperity (X2) have a positive relationship with thel 1945 Constitutionl (Y1), the Republicl of Indonesial (Y2), Bhinneka Tunggal Ika (Y3). By applying the value of the essence of nationality based on the 1945 Constitution, the Republic of Indonesia, and Bhinneka Tunggal Ika PT. Pertamina emphasizes equality, territorial unity, law compliance, focusing on independence, justice and mutual assistance.